THE IMAGES OF UKRAINIAN MODERN EX-LIBRIS - Тупик, Виктор (SWorldJournal, 2020)
The experience of the modern Ukrainian artists of graphic art testifies to the presence of an enormous thematic variety of book-plate. The authors of book signs use in the works the enormous amount of various images, among that the images of the natural a